2020
DOI: 10.1371/journal.pone.0238832
|View full text |Cite
|
Sign up to set email alerts
|

Can participatory approaches strengthen the monitoring of cyanobacterial blooms in developing countries? Results from a pilot study conducted in the Lagoon Aghien (Ivory Coast)

Abstract: Monitoring of cyanobacteria in freshwater ecosystems is a complex task, which is time consuming and expensive due to the chaotic population dynamics and highly heterogeneous distribution of cyanobacteria populations in water bodies. The financial cost constitutes a strong limitation for the implementation of long-term monitoring programs in developing countries, particularly in Africa. The work presented here was performed in the framework of an international project addressing the sustainable monitoring and m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 28 publications
1
5
0
1
Order By: Relevance
“…This study shows that it is possible to develop mesocosm systems at a moderate cost that are also easy to transport and construct in the field. As already observed during a pilot study on citizen monitoring of Lagoon Aghien (Mitroi et al, 2020), we also showed that it is possible to benefit from active local population support during experiments, in particular, support for the installation of the mesocosms and their monitoring when scientific teams were not present on site. These actions occur when these experiments are prepared by these populations.…”
Section: Discussionsupporting
confidence: 82%
“…This study shows that it is possible to develop mesocosm systems at a moderate cost that are also easy to transport and construct in the field. As already observed during a pilot study on citizen monitoring of Lagoon Aghien (Mitroi et al, 2020), we also showed that it is possible to benefit from active local population support during experiments, in particular, support for the installation of the mesocosms and their monitoring when scientific teams were not present on site. These actions occur when these experiments are prepared by these populations.…”
Section: Discussionsupporting
confidence: 82%
“…According to Clum et al (2009) , Pirellula strains are able to attach to cyanobacteria, suggesting that some could originate from the phycosphere and be ingested along with the phytoplankton ( Bi et al, 2019 ). Indeed, Aghien lagoon is experiencing frequent cyanobacterial bloom events ( Mitroi et al, 2020 ). The toxin-producing cyanobacterial genus Planktothrix , recently documented from the cyanobacterial phytoplankton community in Aghien lagoon ( Ahoutou et al, 2021 ) was for example found both in water (yet not dominant) as well as occasionally in fish guts.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we investigated the effect of host versus environmental factors on the structure of gut-associated bacterial communities in four fish species collected from the Aghien lagoon (Ivory Coast). Aghien lagoon is a eutrophic freshwater lagoon and harbors high biomasses of microbial primary producers including potentially toxic cyanobacteria ( Mitroi et al, 2020 ; Ahoutou et al, 2021 ). In the context of an international project addressing the sustainable monitoring of surface water resources used for the production of drinking water, specimens of commonly consumed fish species were collected over a year.…”
Section: Introductionmentioning
confidence: 99%
“…Other visual criteria, such as water color and turbidity can nevertheless be shared indicators between expert and profane grids of water quality lectures. Some interesting citizen science experiences have confirmed that citizens can inform cyanobacteria blooms on lakes and shallow waterbodies in relevant ways (Castilla et al, 2015;Mitroi et al, 2020), thereby complementing the institutional monitoring of the trophic status of these aquatic systems (Hadj et al, 2017). In addition to the aesthetic and visual criteria, other factors play a role in the public perception of hardly transformed ecosystems such as the health benefits related to the possibilities offered by these water bodies to enjoy nature or to provide recreational activities (angling, swimming, boating) (Junker & Buchecker, 2008).…”
Section: Social Perceptions Of Landp Quality and Users' Aesthetic Pre...mentioning
confidence: 99%